PERELEK CULTURE: A SHARING EFFORT IN KUTA VILLAGE - Widiyanti, Sopi Aprilia; Wilodati, Wilodati (Universitas Tanjungpura, 2023)
Perelek is one of the residents' efforts to show their existence by preserving this culture in social life in society. The method used is Literature Study; in collecting research data, the authors collect and analyze various sources through journals, books, and previous research, which are still related to the topic of discussion in this journal article. The results of this study indicate that the Kuta Indigenous Village Community still preserves the Beas Perelek by collecting one spoon of rice per day from each resident, who is collectively by the wife of the head of the local RT. This